2002
DOI: 10.1210/endo.143.3.8696
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/Rho-Kinase Cascade Is Involved in Oxytocin-Induced Rat Uterine Contraction

Abstract: The RhoA/Rho-kinase cascade is involved in various cellular functions, including migration, proliferation, and smooth muscle contraction. We examined the potential role of this pathway in oxytocin-induced uterine contraction. The specific Rho-kinase inhibitor Y-27632 inhibited oxytocin-induced rat uterine contraction on d 21 of pregnancy in a concentration-dependent manner, whereas the extent of this inhibition was reduced in the nonpregnant uterus. Y-27632 had no effect on oxytocin-induced intracellular Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…Oxytocin inhibits the proliferation of human brain tumors (43), breast cancer cells (44), and adenocarcinoma of endometrium (45) via the cyclic adenosine monophosphate-protein kinase A pathway. Tahara et al (46) have reported that the RhoA/Rho-kinase cascade is involved in oxytocin-induced rat uterine contraction. Among the considerable diversity of oxytocin-mediated signaling pathways, the specific pathway that activates cardiogenesis is currently unknown.…”
Section: Fig 4 Immunocytochemical Analysis Of Cardiac Proteinsmentioning
confidence: 99%
“…Oxytocin inhibits the proliferation of human brain tumors (43), breast cancer cells (44), and adenocarcinoma of endometrium (45) via the cyclic adenosine monophosphate-protein kinase A pathway. Tahara et al (46) have reported that the RhoA/Rho-kinase cascade is involved in oxytocin-induced rat uterine contraction. Among the considerable diversity of oxytocin-mediated signaling pathways, the specific pathway that activates cardiogenesis is currently unknown.…”
Section: Fig 4 Immunocytochemical Analysis Of Cardiac Proteinsmentioning
confidence: 99%
“…Furthermore, exposure of human uterine smooth muscle cells to agonists like thromboxane induces an increase in ROCK1 [19]. In rat, mouse, and human myometrium, the ROCK inhibitor Y27632 affected oxytocin-, thromboxane-, and carbachol-induced increases in tension and MYL phosphorylation without a reduction in [Ca 2þ ] i [5,20,21; also see Note Added in Proof]. Recently, the use of Y27632 in pregnant rats with lipopolysaccharide and prostaglandin F2alpha induced preterm labor, leading to lower delivery rates [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, during agonistinduced contractions, the increase in MYL phosphorylation and tension observed is usually higher than the corresponding increase in [Ca 2þ ] i . This increase in calcium-independent tension is termed ''Ca 2þ sensitization'' [4,5]. Dephosphorylation of the phosphorylated MYL by a myosin phosphatase results in relaxation [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes capable of phosphorylating MYPT1 in vitro include ROCK [41], ZIPK [42] and ILK [43]. ROCK-dependent phosphorylation of one or both of these sites has been demonstrated in smooth muscle cells [44][45][46][47] and rat uterine strips [48], and phospho-MYPT1 (Thr 853 ) can be increased during Ca 2 + -sensitization of permeabilized vascular smooth muscle induced by phenylephrine or GTP[S] (guanosine 5-[γ -thio]triphosphate) [47]. However, evidence for phosphorylation of MYPT1 at these sites in human myometrial tissue is lacking, and inhibition of MYLP activity as a method of Ca 2 + -sensitization in this tissue remains speculative.…”
Section: Cpi-17-independent Mechanismsmentioning
confidence: 99%